Some of the legal regulation of land relations in the Republic of Kazakhstan - Yessekeyeva, A.A. (Journal of actual problems of jurisprudence, 2018)
Land Law of Kazakhstan – one of the fastest growing areas of law. Trends, the dynamics of land legislation reflect the legal and political will, conceptual approaches of power on the land issue and, ultimately, are the legal expression of objective processes in the land sector. Conceptual foundations of modern land – legal policy defined by the Constitution of the Republic of Kazakhstan dated August 30, 1995, based on scientific analysis of legislation the author reveals the specific features of the legislative provision of land law in modern Kazakhstan. From the standpoint of the stability of society, sustained and sustainable development of the land issue is not only socio-economic but also a special political significance. On this basis, providing quality and effective legal regulation remains quite urgent task of jurisprudence and legal policy. Land law has always occupied a special place in the legal system, but in the context of increasing the scale of economic turnover of land, involving land and land rights in the sphere of the market, its socio – regulatory value increases. Key words: land, land law, land law, land management, legal regulation.